Fatigue and health-related quality of life depend on the disability status and clinical course in RRMS - Ahvenjarvi Henrik; Niiranen Marja; Simula Sakari; Hämäläinen Päivi; Surcel Heljä-Marja; Remes Anne M.; Ryytty Mervi; Kruger Johanna (ELSEVIER SCI LTD, 2025)
Background: Fatigue is a prominent and disabling symptom of multiple sclerosis (MS), impairing quality of life. The disease course of relapsing remitting MS (RRMS) is individual.
Objectives: We aimed to study the effects of demographic and clinical characteristics, as well as lifestyle risk factors on experienced fatigue and health-related quality of life (HRQoL) among RRMS patients, comparing benign and severe disease types.
Methods: Altogether 198 Finnish RRMS patients were recruited for this real-life cross-sectional study. Self-reported questionnaires were used to evaluate fatigue and HRQoL by using Fatigue Scale for Motor and Cognitive Functions and 15D health-related quality of life questionnaires. Patients were categorized into sub-groups based on the current disability status measured by the Expanded Disability Status Scale (EDSS) cut-off value of 4.5, and by retrospective clinical course divided into benign and aggressive RRMS.
Results: All in all, 73% of the RRMS patients suffered from fatigue. Lower HRQoL had a strong correlation with more prominent fatigue (r =-0.719). Higher EDSS was associated with more prominent fatigue and lower HRQoL in the whole RRMS cohort. Older age at the disease onset was associated with more prominent fatigue and decreased HRQoL in the groups of aggressive RRMS and EDSS > 4.5. In the groups of EDSS & LE; 4.5 and benign RRMS, a higher number of used disease-modifying treatments (DMTs) was associated with more pronounced fatigue and reduced HRQoL. In addition, higher BMI was associated with lower HRQoL in patients with benign RRMS. Side effects (45 %) and lack of efficacy (26 %) were the most common reasons for discontinuing a DMT. Cessation due to side effects was the only reason that was significantly associated with more prominent fatigue and lower HRQoL. Use of nicotine products, gender, or disease duration were not associated with fatigue or HRQoL.
Conclusions: Individuals with severe RRMS and higher EDSS scores are more prone to experience fatigue and lower HRQoL. In addition, fatigue and lower HRQoL are more commonly observed among RRMS patients with older age at disease onset and in those with multiple DMT switches.